2011
DOI: 10.3892/ol.2011.245
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer patients in Libya: Comparison with European and central African patients

Abstract: Abstract. The present study evaluated the incidence of breast cancer in Libya and described the clinicopathological and demographic features. These features were then compared with corresponding data from patients from sub-Saharan Africa (Nigeria) and Europe (Finland). The study consisted of 234 patients with breast carcinoma, admitted to the African Oncology Institute in Sabratha, Libya, during the years [2002][2003][2004][2005][2006]. The pathological features were collected from pathology reports, patient h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 14 publications
20
49
1
Order By: Relevance
“…This is consistent with some studies done in Ghana [9] [32] [33] and Africa [34] [35]. Breast cancer mortality was found to be correlated to the stage at diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with some studies done in Ghana [9] [32] [33] and Africa [34] [35]. Breast cancer mortality was found to be correlated to the stage at diagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, Nigerian and Libyan results are near each other. In premenopausal patients, SMI shows statistical significance between Libyan and Nigerian and between Libyan and Finnish tumours, which may reflect biological differences between Central African, North African, and European population, possibly explained by variation in genetic marker distribution in these populations [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by that the peak of oestrogen effect is expected in patients with age below 40, because this period shows high level of serum oestrogen, and the fraction of unmarried female individual was higher among the Libyan breast cancer patients as compared to the North African population (23.8% and 15–21%, resp.) [29]. On other hand, the high mitotic activity of Libyan patients older than 49 years can be explained by diagnosis delay which is a serious problem in Libya [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A marked increase in the annual number of breast cancer among Iraqi women between 2000 and 2009, this most probably due to the improvement awareness in connection with the Iraqi National Breast Cancer Research Program that began in 2000, Improvement of Iraqi national cancer research center data collection, opening of new breast cancer screening mammograms that were implemented from 2000 onward led to increased mammography screening. In a report from Arab countries, show that the rising in incidence in Arab countries and the change may be due to a westernized life style including dietary habits, lack of exercise, delay of age of marriage, women have their diagnosis of breast cancer delayed because of lack of awareness, social customs and most important is a low index of suspicion from primary care (Saadat, 2008 (Lakkis et al, 2010), 44.5-47.15% in Jordan (Tarawneh et al 2009, Tarawneh et al 2011), Kuwait 47.5% (Al-Madouj et al, 2011, and less than those observed in UAE 56.7%,, Qatar 59.7%, Saudi 58.8(AlLibya (71%) (Boder et al, 2011), 74% Sudan (Elgaili et al, 2010), Iran 67.5% (Montazeri et al, 2008). An article from developing countries including Arab countries, show that breast cancer among women with a young age of around 50 years at presentation (El Saghir, et al, 2007).…”
Section: Iraq and United Kingdom In 2009mentioning
confidence: 99%